On Generalized Weyl Fractional $q$-Integral Operator of General Class of $q$-Polynomials - Shimelis, Biniyam; Suthar, D.L. (Discontinuity, Nonlinearity, and Complexity, 2026)
In the present paper, we obtain generalized Weyl fractional $q$-integrals of the general class of $q$-polynomials and demonstrate their use by studying $q$-Konhouser biorthogonal polynomial, $q$-Jacobi polynomials and basic analogue of the Kampé de Fériet function. Polynomials have been obtained as a particular case of our major findings.